SPACE OCCUPYING LESION - Hutajulu, Maria Margaeta (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2018)
Abstract: SOL is a extended lesion in brains including tumor, hematoma and abscesses. Because the cranium is stiff with a fixed volume,then the lesions will increase the intracranial pressure. A lesion that extends first will be accommodated by removing the cerebrospinal fluid from the cavity of the cranium. Eventually venous will compression and disorders braincirculation and cerebrospinal fluid will appears, so the intracranial pressure will increase. Venosa congestion gives rise to increased production and decreased absorption of cerebrospinal fluid and increase the volume and going back to things like above.1 The position of the lesion in the brain space urges can have a dramatic influence on the signs and symptoms. For example a lesion can clog the spaces flow urges out of cerebrospinal fluid or directly pressing on a large vein, makethe intracranial pressure increased rapidly. Signs and symptoms allows doctors to localize the lesion will depend on the occurrence of a disorder in the brain as well as the degree of tissue damage caused by nerve lesion. Great head pain, possibly due to stretching durameter and vomiting due to pressure on the brain stem is a common complain. A lumbar pungsi should not be performed on patients suspected intracranial tumors. Spending on the cerebrospinal fluid will lead to the onset of sudden shifts hemispherium cerebri through notch into posterior fossa cranii cerebelli or herniation of the medulla oblongata and serebellum through the foramen magnum. At this time the CT-scan and MRI is used to enforce a diagnose.Keywords: Space, Occupying, Lesion